The Influence Of E-Servicescape on Behavioral Intention with Customer Satisfaction As A Mediating Variable (Survey of active users of Pegipegi mobile application in Indonesia) - Rahayu, Ismi; Pandia, Suka Prayanta; Siswhara, Gita (Universitas Pendidikan Indonesia (UPI), 2024)
A service in the field of hospitality and tourism depends largely on the level of visits of customers who have different needs, desires, and characteristics. In taking an action, behavioral intention becomes a direct determinant of consumer behavior that connects consumers with themselves with actions that will be carried out in accordance with consumer wishes and expectations that they will show in the future. Behavioral intention is closely related to customer satisfaction because the satisfaction felt by consumers will have an impact on attitudes towards products or services and consumer purchases in the future. There have been many empirical studies that state that behavioral intention and customer satisfaction can show the superior power of the company. Based on the above, conducting research on behavioral intention will greatly help the company in maintaining excellence and maintaining the company's existence. The purpose of this study is to obtain an overview and influence of the e-servicesape on behavioral intention with customer satisfaction as a mediating variable in active users of Pegipegi mobile application in Indonesia. The research method used is a quantitative method with descriptive and verifiative research types. The study was conducted by setting a sample of 384 application users through questionnaires as data collection. The study used SEM (Structural Equation Model) analysis techniques with AMOS 20.0 software and SPSS for windows version 25.0. Tests that have been conducted suggest that e-servicescape has a significant influence simultaneously on behavioral intention with customer satisfaction as a mediation variable.